Phagocytosis of Mycoplasma salivarium by human polymorphonuclear leukocytes and monocytes. - Parkinson, C F (1975)
Mycoplasmacial activity was exhibited by human peripheal blood leukocytes in the absence of detectable specific antiserum. After incubation of varying concentrations of Mycoplasma salivarium with leukocytes, changes in colony-forming units (CFU) of this species per millilter occurred. The most noticeable decrease in CFU per milliliter was then the incubation mixtures contained five mycoplasmas per leukocyte. At this ratio, the mycoplasmacial min of incubation. Continued incubation demonstrated a tenfold decrease in CFU per milliliter by 4 h. Electron micrographs of incubated mixtures of human leukocytes and M. salivarium showed this mycoplasma to be phagocytized by monocytes and neutrophils whenever mutual contact or pseudopodial formation occurred. The process was continuous. Numerous phagocytic vacuoles developed which contained multiple ingested microorganisms. After the cytoplasmic granules of the leukocytes fused with the phagocytic vacuole, the phagocytized mycoplasmas became disrupted and unrecognizable.